A randomized controlled study to evaluate and compare Truview blade with Macintosh blade for laryngoscopy and intubation under general anesthesia - Ramesh T Timanaykar; Lakesh K Anand; Sanjeev Palta (Wolters Kluwer Medknow Publications, 2011)
Background: The Truview EVO2 TM laryngoscope is a recently introduced device with a unique blade that provides a magnified laryngeal view at 42° anterior reflected view. It facilitates visualization of the glottis without alignment of oral, pharyngeal, and tracheal axes. We compared the view obtained at laryngoscopy, intubating conditions and hemodynamic parameters of Truview with Macintosh blade. Materials and Methods: In prospective, randomized and controlled manner, 200 patients of ASA I and II of either sex (20-50 years), presenting for surgery requiring tracheal intubation, were assigned to undergo intubation using a Truview or Macintosh laryngoscope. Visualization of the vocal cord, ease of intubation, time taken for intubation, number of attempts, and hemodynamic parameters were evaluated. Results: Truview provided better results for the laryngeal view using Cormack and Lehane grading, particularly in patients with higher airway Mallampati grading (P < 0.05). The time taken for intubation (33.06±5.6 vs. 23.11±57 seconds) was more with Truview than with Macintosh blade (P < 0.01). The Percentage of Glottic Opening (POGO) score was significantly higher (97.26±8) in Truview as that observed with Macintosh blade (83.70±21.5). Hemodynamic parameters increased after tracheal intubation from pre-intubation value (P < 0.05) in both the groups, but they were comparable amongst the groups. No postoperative adverse events were noted. Conclusion: Tracheal intubation using Truview blade provided consistently improved laryngeal view as compared to Macintosh blade without the need to align the oral, pharyngeal and tracheal axes, with equal attempts for successful intubation and similar changes in hemodynamics. However, the time taken for intubation was more with Truview.